2021
DOI: 10.1007/s13555-021-00559-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose Adjustment of Biologic Treatments for Moderate-to-Severe Plaque Psoriasis in the Real World: A Systematic Review

Abstract: Introduction Dose escalation and reduction of biologic treatments are frequent in clinical practice. The aim of this systematic review is to summarise evidence on dose adjustment of biologic treatments for moderate-to-severe plaque psoriasis in the real-world. Methods A systematic review of real-world evidence on dose adjustment of biologics for plaque psoriasis was performed. Searches were conducted in BIOSIS Previews ® , Embase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Initiation of an adjuvant treatment or dose escalation (by shortening the dosing interval of a biologic drug) frequently occurs in real‐world biologic treatment processes usually because of inadequate primary response or loss of efficacy over time 27 . Although these treatment modifications can have safety concerns, none of the patients in our study experienced treatment‐modification‐related adverse events, and most of them gained/regained good PASI scores.…”
Section: Discussionmentioning
confidence: 85%
“…Initiation of an adjuvant treatment or dose escalation (by shortening the dosing interval of a biologic drug) frequently occurs in real‐world biologic treatment processes usually because of inadequate primary response or loss of efficacy over time 27 . Although these treatment modifications can have safety concerns, none of the patients in our study experienced treatment‐modification‐related adverse events, and most of them gained/regained good PASI scores.…”
Section: Discussionmentioning
confidence: 85%
“…KEGG was widely employed to screen biological pathways (31). DO enrichment analysis was commonly used to identify large-scale disease enrichment research by clusterProfiler, GSEABase (version 1.58.0) (32), DOSE (version 3.22.0) (33), and enrichplot package in R language (adjusted P<0.05). GSEA analysis was applied to investigate potential differences in biological processes and signaling pathways in GEO merged dataset and TCGA-PRAD cohort by the 'clusterProfiler and enrichplot package' in R software.…”
Section: Gene Ontology (Go) Biological Function the Kyotomentioning
confidence: 99%
“…[1][2][3][4] Although no guidelines exist to date for the off-label use of biologic dose modification, it is a common clinical practice in the long-term treatment of moderate-to-severe plaque psoriasis, in which escalation is more frequently reported than reduction for biologic agents. [5][6][7][8] The information about SEC dose reduction (SEC-DR) in psoriasis treatment in a real-life dermatological setting is limited and only marginally mentioned. 9,10 Only two studies informed about dose adjustment for secukinumab: One of them showed that 52% of patients initiated on a lower dose (150 mg) than that recommended under Summary of Product Characteristic (SPC) 9 ; the other only focused on dose escalation.…”
Section: Introductionmentioning
confidence: 99%
“…The anti‐IL‐17A monoclonal antibody secukinumab (SEC) has shown long‐lasting efficacy Psoriasis Area and Severity Index (PASI) 90/100 responses and safety in moderate‐to‐severe plaque psoriasis in several clinical trials and daily practice 1–4 . Although no guidelines exist to date for the off‐label use of biologic dose modification, it is a common clinical practice in the long‐term treatment of moderate‐to‐severe plaque psoriasis, in which escalation is more frequently reported than reduction for biologic agents 5–8 . The information about SEC dose reduction (SEC‐DR) in psoriasis treatment in a real‐life dermatological setting is limited and only marginally mentioned 9,10 .…”
Section: Introductionmentioning
confidence: 99%